Pediatric Cancer Survivors 2017
DOI: 10.5772/67040
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Craniofacial Effects on Childhood Cancer Survivors

Abstract: The availability and adoption of modern therapeutic protocols for childhood cancer have continuously reduced the mortality rate of childhood malignancies in most countries over the past decades. Children being treated for cancer are actively growing, creating unique problems not only in the short-term but also in the long-term development of both the orofacial hard and soft tissue. Complications during and after cancer therapy depend on the type of malignancy, age at diagnosis, and the drugs used during the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 112 publications
(139 reference statements)
0
11
2
Order By: Relevance
“…In the current study, 62 teeth of 21 patients (17%) displayed some form of hypocalcification and hypoplasia. Several studies indicated higher rates of this dental alteration than observed in our cohort 14,15,22,42 . Twenty-one patients (17.4%) in the current study displayed microdontia in contrast to 0.8%-1.7% 38 in healthy populations.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…In the current study, 62 teeth of 21 patients (17%) displayed some form of hypocalcification and hypoplasia. Several studies indicated higher rates of this dental alteration than observed in our cohort 14,15,22,42 . Twenty-one patients (17.4%) in the current study displayed microdontia in contrast to 0.8%-1.7% 38 in healthy populations.…”
Section: Discussioncontrasting
confidence: 43%
“…Acute oral effects include: mucositis, bleeding, taste alterations, secondary infections, salivary gland dysfunction, periodontal conditions and neurotoxicity 2,9,10 . Late oral phenomena include: exacerbated dental caries, temporomandibular dysfunction, osteoradionecrosis, cranio-dental development, dental anomalies and oral graft versus host disease 2,[9][10][11][12][13][14][15][16] . Children are particularly vulnerable to the harmful effects of radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuation of severe or long-term upsets may damage root formation, thus leading to a shortened or tapered root. Root development plays a dominant role in the eruption; disturbance to a tooth root might impair tooth eruption and occlusion 9 . The rst sign of dental disturbances can be expected within one or two years of anticancer treatment 9 .…”
Section: Introductionmentioning
confidence: 99%